2014
DOI: 10.1371/journal.pone.0086753
|View full text |Cite
|
Sign up to set email alerts
|

3 β-Hydroxysteroid-Δ 24 Reductase (DHCR24) Protects Neuronal Cells from Apoptotic Cell Death Induced by Endoplasmic Reticulum (ER) Stress

Abstract: 3β-Hydroxysteroid-Δ24 reductase (DHCR24) is an endoplasmic reticulum (ER)-localized multifunctional enzyme that possesses anti-apoptotic and cholesterol-synthesizing activities. Accumulating evidence suggests that ER stress is involved in the pathogenesis of neurodegenerative disease. In this study, we investigated whether DHCR24 may function as a neuroprotective protein under ER stress. Neuroblastoma N2A cells were infected with adenovirus expressing myc-tagged DHCR24 (Ad-DHCR24) or lacZ (Ad-lacZ, serving as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 42 publications
(64 reference statements)
2
31
0
Order By: Relevance
“…A close inspection of the GO category "oxidation-reduction process" revealed an ethanol-induced up-regulation of Dhcr24 shown to exert a neuroprotective effect against reactive oxygen species resulted from endoplasmic reticulum stress (Lu et al, 2014). The down-regulation of Cp, an important antioxidant molecule, is in accordance to previous studies on hippocampi after chronic ethanol exposure (Saito et al, 2002).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A close inspection of the GO category "oxidation-reduction process" revealed an ethanol-induced up-regulation of Dhcr24 shown to exert a neuroprotective effect against reactive oxygen species resulted from endoplasmic reticulum stress (Lu et al, 2014). The down-regulation of Cp, an important antioxidant molecule, is in accordance to previous studies on hippocampi after chronic ethanol exposure (Saito et al, 2002).…”
Section: Discussionsupporting
confidence: 87%
“…1 and 3A). Overexpression of Dhcr24 was shown to inhibit apoptotic cell signaling (Lu et al, 2014), hence it seems reasonable to assume that the observed upregulation of Dhcr24 is a counterbalance that prevents the commitment on the activated apoptotic pathway in CGCs.…”
Section: Discussionmentioning
confidence: 99%
“…DHCR24 protein is of particular interest and potentially relevant in the context of NPC disease. It is an ER-localized multifunctional enzyme and has shown to protect neuronal cells from apoptosis induced by ER stress (27). Interestingly, apoptosis is one of the enriched GO terms in the analysis of DEPs data set with Ontologizer ( Fig.…”
Section: Validation Of Tmt Results Of Selective Proteins From Deps Datamentioning
confidence: 99%
“…DHCR24 (also known as Seladin-1) is involved in the final step of cholesterol biosynthesis, catalyzing the conversion of desmosterol to cholesterol by saturating the C-24,25 double bond in its sidechain (28). DHCR24 suppresses the excess generation of intracellular ROS from ER stress and functions as an antiapoptotic and neuroprotective protein (27). Therefore, we examined the effect of various classes of drugs that are currently being tested for efficacy in NPC treatment, such as cyclodextrins (HPCD/M␤CD), HDACIs (Cl-994, SAHA, VPA), antioxidant NAC, and an oxysterol derivative pharmacological chaperone (mo56HC) on the expression level of SOD2 and DHCR24 in NPC1 I1061T cells.…”
Section: Effect Of Potential Npc Drugs On Expression Of Sod2 and Dhcrmentioning
confidence: 99%
“…For each new model, we repeated the complete process of variable selection in purine biosynthesis (Lane and Fan, 2015;Li et al, 2007), and TMEM97 (part of GPS) is a regulator of cholesterol levels (Bartz et al, 2009), which is further described to be involved in cell cycle regulation, cell migration and invasion in a glioma cell model according to RNA interference experiments (Qiu et al, 2015). DHCR24 (another GPS transcript) represents a multifunctional enzyme localized to the endoplasmic reticulum (ER) that catalyzes the final step in cholesterol-synthesis (Waterham et al, 2001) but also possesses anti-apoptotic activity as, for example, shown for neuronal cells under ER stress (Lu et al, 2014). PLK1, a kinase, has been shown to be phosphorylated in response to TLR activation and results from RNA interference suggested that PLK1 signaling was involved in the TLR-induced inflammatory response (Hu et al, 2013).…”
Section: Prediction Of An Independent Test Setmentioning
confidence: 99%